THE EFFECT OF PROFESSIONAL THEMATIC PLAY ON CHILDREN'S SOCIAL AND EMOTIONAL DEVELOPMENT IN TK AT-TAUBAH JOMBANG - siti indatul laili; Tri Peni (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
During the preschool age, playing becomes a primary activity that is inseparable from children's lives. A relevant game to stimulate children's social and emotional development is professional thematic play. The purpose of this research was to examine the influence of professional thematic play on children's social and emotional development at AT-Taubah Kindergarten, Jombang. The design of this research used a one-group pre-post test. The population in this research was all mothers and children at AT-Taubah Kindergarten, Jombang, totaling 84 children. The sampling technique used was purposive sampling. The samples in this research were some mothers and children at AT-Taubah Kindergarten, Jombang, totaling 46 children. The measuring instrument used was a questionnaire with test results of 100% validity and reliability, with ρ= 0.738. Data processing, starting from editing, coding, scoring, and data analysis, was carried out using the Wilcoxon signed-rank test. The research results showed that children with good social-emotional development experienced an increase after engaging in professional-themed play, from 22 respondents (48%) to 41 respondents (89%). The Wilcoxon signed-rank test showed a ρ=0.000. Professional themed play provides children with the opportunity to explore their emotions, enabling them to better understand and manage their emotions.